2004
DOI: 10.1051/0004-6361:20031740
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical instability strips forδScuti andγ Doradus stars

Abstract: New theoretical instability strips for δ Sct and γ Dor stars are presented. These results have been obtained taking into account the perturbation of the convective flux following the treatment of Gabriel (1996). For the first time, the red edge of the δ Sct instability strip for non-radial modes is obtained. The influence of this time-dependent convection (TDC) on the driving of the γ Dor gravity modes is investigated. The results obtained for different values of the mixing-length parameter α are compared for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
187
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(198 citation statements)
references
References 17 publications
11
187
0
Order By: Relevance
“…Theoretical calculations by Dupret et al (2004) also successfully reproduced the observed instability strip of the γ-Doradus stars, at least as it was known before the observations made by Kepler. Indeed, recently the Kepler satellite detected a large number of hybrid δ Scuti -γ Doradus pulsators lying on the left side of the blue edge of γ Doradus (Balona and Dziembowski, 2011;Balona, 2014), as shown in Fig.…”
Section: Convective Flux Blocking Mechanismsupporting
confidence: 67%
See 1 more Smart Citation
“…Theoretical calculations by Dupret et al (2004) also successfully reproduced the observed instability strip of the γ-Doradus stars, at least as it was known before the observations made by Kepler. Indeed, recently the Kepler satellite detected a large number of hybrid δ Scuti -γ Doradus pulsators lying on the left side of the blue edge of γ Doradus (Balona and Dziembowski, 2011;Balona, 2014), as shown in Fig.…”
Section: Convective Flux Blocking Mechanismsupporting
confidence: 67%
“…4.3) must be considered. Dupret et al (2004) calculations based on TDC finally confirmed the effectiveness of the convective flux blocking mechanism (see also Dupret et al, 2005).…”
Section: Convective Flux Blocking Mechanismmentioning
confidence: 65%
“…The dot-dash line is a model for a star with an initial mass of 1.0M ⊙ in a binary system with a 0.9M ⊙ companion, orbital separation of 4.8R ⊙ and metallicity Z=0.008. The instability strip for δ-Scuti-type pulsations with radial order k = 4 is indicated by light-grey shading (Dupret et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 2 shows the log T eff versus log L/L diagram of our programme stars (Table 1) together with the borders of the δ Scuti and γ Doradus instability strips taken from Breger & Pamyatnykh (1998) and Dupret et al (2004), respectively. Four stars (HD 23392, HD 36726, HD 261904 and HD 294253) are well outside the instability strips whereas HD 90821 is just on the edge.…”
Section: Discussionmentioning
confidence: 99%